2008
DOI: 10.1111/j.1540-8159.2008.01171.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Judgment Versus Decision Analysis for Managing Device Advisories

Abstract: We found that despite a fairly conservative device replacement strategy for advisories, we still replaced more devices when it was not the preferred device management strategy predicted by a decision analysis model. This study demonstrates that even when risks and benefits are being considered by experienced clinicians, a formal decision analysis can help to develop a systematic evidence based approach and potentially avoid unnecessary procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…Six of the seven included studies reported data collected retrospectively (914), and one reported prospectively collected data (15). Three were multicenter (10,11,13) and four were single center (9,12,14,15).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Six of the seven included studies reported data collected retrospectively (914), and one reported prospectively collected data (15). Three were multicenter (10,11,13) and four were single center (9,12,14,15).…”
Section: Resultsmentioning
confidence: 99%
“…Three were multicenter (10,11,13) and four were single center (9,12,14,15). All but one reported experience within the US only(10), however in all cases, advisories and recalls were issued by the FDA rather than a local or international regulator of medical devices.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations